London 2012 - Experience and legacy - Nicholl, L. (8. International Forum on Elite Sport, Rio de Janeiro, Brasil, August 26, 2013 - August 31, 2013, 2013)
Vision and goal: For the UK to be at least as competitive in Rio 2016 as we are now, but with a stronger, more sustainable high performance sport system. The first nation in recent history to win more medals at the next Games.